AB0537 Superior low disease activity and remission rates when rituximab is initiated after the first anti-TNF failure: Real life data. (23rd January 2014) - Ancuta, I.; Codreanu, C.; Ionescu, R.; Parvu, M.; Bojinca, M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disorder, affecting patient's quality of life. Therefore the National Health Insurance House invests important budgets each year for RA treatments, while not all drugs and/or therapeutic approaches proved to be effective for the vast majority of patients. Finding treatment protocols that bring most benefits for the patients becomes thus an important concern and topic for research. Objectives: Compare efficiency of two different RA therapy approaches: (1) switching to Rituximab (RTX) after a first anti-TNF failure or (2) switching to RTX after a second/third anti-TNF failure. Methods: Longitudinal (2002 up to date), observational, population-based, cohort study. The analysis was performed for 400 RA patients over 18 years old: 75.1% female (average age 54), 24.9% male (average age 52), all having an anti-TNF α medication as first treatment stage for 2.5 years (average). In the second stage, 208 patients (Group 1) were switched to RTX after the initial anti-TNFα failure, having a median 2.3 RTX cycles (2g at 24 weeks). All the remaining 192 patients (Group 2) continued with one more anti-TNF (10.8 months) and 32 of them had also a third one (7.9 months). Only then, Group 2 continued with RTX therapy for a median 2.2 cycles. We evaluated the effectiveness of the 2 approaches using: DAS28, Δ DAS28, and EULAR response. Results: For all 400 patients average DAS28 was 6.55 before RTX therapy, and 3.50 after 2 complete RTX cycles (12 months). For Group 1, DAS28 decreased from 6.31 to 3.25 (medium values) after 2 complete RTX cycles (N=208). For Group 2 we noticed an increase of DAS28 during the cure, medium ΔDAS28 reached 0.9 thus evidencing development of resistance to the anti-TNF medication. DAS28 decreased consistently for all patients in RTX therapy but reached its lowest value for Group 1 patients: after the first RTX cycle, ΔDAS28 = - 2.3. All patients receiving RTX, achieved LDA or remission, but for Group 1, these results have been obtained sooner and in a higher percentage. After 2 RTX cycles (12 months) Group 1 obtained 36.5% LDA and 15.4% remission, vs. only 15.1% LDA and 8.3% remission in Group 2. At the end of the study (five RTX cycles), 91% of Group 1 patients experienced LDA and remission (54.9% remission) vs. 80.8% of the patients in Group 2 (40.4% remission). Conclusions: Introducing RTX after the first anti-TNF therapy proved to be the most effective option, leading to cumulating of clinical benefits (fast LDA or remission) and to consolidation of lower DAS28 response with each following RTX therapy. This strategy proved to lead to a very good EULAR response, sooner and better than the RTX therapy initiated only after 2 or 3 anti-TNF treatments. The clinical response is very good irrespective of the rheumatoid factor status, and no resistance appeared to the RTX treatment. Based on these results, we consider RTX treatment after the first anti-TNF failure as a preferred treatment option and in terms of clinical response it follows the EULAR–ACR principles on RA treat-to-target. Disclosure of Interest: None Declared